2021
DOI: 10.1080/13504851.2021.1963408
|View full text |Cite
|
Sign up to set email alerts
|

Government revenue, quality of governance and child and maternal survival

Abstract: This paper considers the effect of government revenue and the quality of governance on the under-five and maternal survival rates. A non-linear panel data study was undertaken using annual data for every country in the world. The study's broad conclusion is that while government resources, measured as total revenue received by a country's government, is essential, the quality of governance is even more critical in determining a good outcome for both mother and child.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…In another study, it's mentioned that the quality of governance is even more critical in determining a good outcome for both mother and child. 28 This evidence was coherent to our finding that showed the strong negative association between governance and mortality rate among newborns (-0.92) and children under-five (-0.89). In our study results, Myanmar, Lao, Timor-Leste, and Cambodia were the four countries with the lowest government effectiveness, and also the countries with the highest children's mortality rates in the Southeast Asia region during the 2015 to 2019 period.…”
Section: Discussionsupporting
confidence: 91%
“…In another study, it's mentioned that the quality of governance is even more critical in determining a good outcome for both mother and child. 28 This evidence was coherent to our finding that showed the strong negative association between governance and mortality rate among newborns (-0.92) and children under-five (-0.89). In our study results, Myanmar, Lao, Timor-Leste, and Cambodia were the four countries with the lowest government effectiveness, and also the countries with the highest children's mortality rates in the Southeast Asia region during the 2015 to 2019 period.…”
Section: Discussionsupporting
confidence: 91%
“…Well-governed countries are more likely to encourage business sector development and investment, enjoy economic growth [23,24], and have robust institutions and political stability [25,26]. Thus, the impact of any additional government revenue is significantly amplified in well-governed countries, especially when revenue is scarce [27]. Indeed, there is a two-way relationship between government revenue and governance, which drives a virtuous circle and improves the generation of further revenue and the allocation and efficient use of additional resources [15].…”
Section: Government Revenue Child Rights Governance and The Sustainab...mentioning
confidence: 99%
“…Any additional corporate tax could play a critical role in lower-income countries as the relationship between government revenue per capita and progress toward the SDGs is highly non-linear, and small increases can have large effects, when government revenue per capita is small [34,35]. In addition, an empirical study by Gaspar et al identified a tax to Gross domestic product (GDP) tipping point.…”
Section: The Role Of Corporate Taxes In Sdg Progressmentioning
confidence: 99%